Development and Interplay of Two Orthogonal Fault Systems in the NW Qaidam Basin, Northern Tibetan Plateau - Huang, Kai; Wu, Lei; Zhao, Haifeng; Zhang, Junyong; Zhang, Yongshu; Xiao, Ancheng; Chen, Yan; Chen, Hanlin (Frontiers in Earth Science, 2021)
How fold and thrust belts (FTBs) evolve over time and space in a transpressional regime remains an unevaluated issue. Based on high-resolution 3D seismic reflection data and remote sensing images, we herein present a detailed structural analysis of the Cenozoic faults in the NW margin of the Qaidam Basin that is bounded to the north by the left-reverse Altyn Tagh fault system. Two sets of orthogonal, basement-involved faults with contrasting geometries, kinematics, and temporal development are identified. One set consists of generally E-W-striking, N-dipping, reverse faults with a component of sinistral shear. They are parallel or subparallel to the Altyn Tagh fault system, led to southward tilting of the basement, and formed a local unconformity between the middle Miocene Shangyoushashan formation and underlying strata. They developed in an out-of-sequence order, and were mostly active during 43.8 – 15.3 Ma but in relatively tectonic quiescence with limited weak reactivation since then. The second set is mainly composed of the NNW-striking reverse faults with dextral shear components. They are approximately perpendicular to the Altyn Tagh fault system, and intensively active since ~15.3 Ma, much later than the initiation of the E-W-striking faults. Together with published results, we ascribe the development of these two sets of orthogonal faults as the transition from transpression to left-slip on the central segment of the Altyn Tagh fault system. The two fault sets interplayed with each other in two ways: (1) the older E-W-striking faults were offset by younger NNW-striking faults, and (2) the younger NNW-striking faults curved to link with the preexisting E-W-striking faults. Our findings reveal that transpressional-dominated FTBs evolve in a more complicated way than the contractional-dominated ones, and more site-based case studies are needed to reveal the underlying primary principles.